Entrepreneurship in informal economy: a study in Kelantan, Malaysia - Mohammad Shaari, Amirul Ashraf; Mohan, Kannigamalar; Lim, Hui Shan; Mu, Yue Lun (2015)
The main aim of this study has been to investigate the reasons that influence the performance of informal enterprise in Kelantan. To achieve this goal, there are few variables and factors that had been looked upon. The variables are as follows, entrepreneurial skills, experiences, level of competitiveness, entrepreneurial traits, and financial resources. The quantitative research was used in this research whereby 160 questionnaires were distributed to 160 respondents who are informal entrepreneurs in Kelantan. In addition, the Statistical Package for Social Sciences (SPSS) version 22.0 was utilized for data analysis. The results showed the performance in informal enterprise was influenced by entrepreneurial skills, experiences, level of competitiveness, entrepreneurial traits, and financial resources.